Compressive strength of concrete in structural elements (Research, Society and Development, 2024)
In the present study, an evaluation of the structural elements, as well as the performance of the concrete, was conducted through sclerometry tests. The main objective was to evaluate the estimated surface resistance of hardened concrete in eight reinforced concrete pergolas in the Porto Velho Alternative Space, using non-destructive equipment and methods, in order to maintain the integrity of the structure after analysis. The evaluation of the quality of the material was carried out through tests using the Schmitd method to obtain the sclerometric indices. The sclerometric indices resulted in compressive strength ranging from 24 MPa to 44 MPa for the columns and 19 MPa to 32 MPa for the beams.